DEVELOPMENT OF MACROMEDIA FLASH-BASED INTERACTIVE LEARNING MULTIMEDIA IN REFRIGERATION SYSTEMS TO IMPROVE STUDENT LEARNING OUTCOMES - Ikhsani, Fahry Nur Khairad; Sumardi, Kamin (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2023)
In order to capture students' interest and improve the effectiveness of learning activities, media must be included in the educational process. The PPE (Planning, Production, and Evaluation). At SMK Negeri 1 Cimahi, the refrigeration system was the topic of a trial in class XI-TPTUP B. 36 students make up the samples. Tests and questionnaires served as the instruments. Interactive learning multimedia built on Macromedia flash was deemed "Very Eligible" with a media feasibility test percentage of 83,35%, according to the results. Acquisition of the 82.5% material due diligence percentage and "Very Eligible" material status. Macromedia flash-based interactive learning multimedia has been well-received. The utilization of interactive learning multimedia based on Macromedia flash is strongly supported by 87,22% of students. The acquisition of an N-Gain value of 0.58 and placement in the moderate category show that interactive learning multimedia built on Macromedia flash is also capable of enhancing student learning outcomes.